MANAJEMEN BERBASIS DATA DALAM PENDIDIKAN ISLAM: PEMANFAATAN LEARNING ANALYTICS UNTUK PENGAMBILAN KEPUTUSAN STRATEGIS - Nailul Muna; Fitriani; M. Fadli; Mahyiddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology in the last two decades has driven fundamental changes in the educational evaluation system. Conventional paper-based and result-oriented evaluations are no longer sufficient to represent the complexity of 21st-century learners competencies. This study aims to conceptually examine the transformation of educational evaluation in the digital era through the integration of learning reflection dan Learning Analytics (LA). The method used is a literature review (conceptual study) with content analysis techniques on various reliable scientific sources. The results indicate that traditional reflection processes are often subjective, abstract, dan late to be realized by students. The integration between LA dan learning reflection gives rise to a new concept called Reflective Learning Analytics or data-driven reflection. Through the Student Dashboard functionality, LA acts as a "digital mirror" that reflects students' learning behavior honestly dan accurately through real-time feedback. Despite offering revolutionary opportunities, the implementation of LA faces challenges in terms of data privacy issues, data literacy gaps, dan technical infrastructure readiness. This study concludes that digital evaluation transformation is not merely about digitizing measurement tools, but represents a paradigm shift toward a data-driven, humanistic, and adaptive evaluation model.